Interleukin 35 protects cardiomyocytes following ischemia/reperfusion-induced apoptosis via activation of mitochondrial STAT3. (23rd February 2021) - Zhou, Fengyun; Feng, Ting; Lu, Xiangqi; Wang, Huicheng; Chen, Yangping; Zhang, Qiuxia; Zhang, Xinlu; Xiu, Jiancheng
Abstract: Mitochondrial reactive oxygen species (mtROS)-induced apoptosis has been suggested to contribute to myocardial ischemia/reperfusion injury. Interleukin 35 (IL-35), a novel anti-inflammatory cytokine, has been shown to protect the myocardium and inhibit mtROS production. However, its effect on cardiomyocytes upon exposure to hypoxia/reoxygenation (H/R) damage has not yet been elucidated. The present study aimed to investigate the potential protective role and underlying mechanisms of IL-35 in H/R-induced mouse neonatal cardiomyocyte injury. Mouse neonatal cardiomyocytes were challenged to H/R in the presence of IL-35, and we found that IL-35 dose dependently promotes cell viability, diminishes mtROS, maintains mitochondrial membrane potential, and decreases the number of apoptotic cardiomyocytes. Meanwhile, IL-35 remarkably activates mitochondrial STAT3 (mitoSTAT3) signaling, inhibits cytochrome c release, and reduces apoptosis signaling. Furthermore, co-treatment of the cardiomyocytes with the STAT3 inhibitor AG490 abrogates the IL-35-induced cardioprotective effects. Our study identified the protective role of IL-35 in cardiomyocytes following H/R damage and revealed that IL-35 protects cardiomyocytes against mtROS-induced apoptosis through the mitoSTAT3 signaling pathway during H/R.